Induction of hypertension blunts baroreflex inhibition of vasopressin neurons in the rat. (5th October 2015) - Han, Su Young; Bouwer, Gregory T.; Seymour, Alexander J.; Korpal, Aaron K.; Schwenke, Daryl O.; Brown, Colin H.
Abstract: Vasopressin secretion from the posterior pituitary gland is determined by action potential discharge of hypothalamic magnocellular neurosecretory cells. Vasopressin is a potent vasoconstrictor, but vasopressin levels are paradoxically elevated in some patients with established hypertension. To determine whether vasopressin neurons are excited in hypertension, extracellular single‐unit recordings of vasopressin neurons from urethane‐anaesthetized Cyp1a1‐Ren2 rats with inducible angiotensin‐dependent hypertension were made. The basal firing rate of vasopressin neurons was higher in hypertensive Cyp1a1‐Ren2 rats than in non‐hypertensive Cyp1a1‐Ren2 rats. The increase in firing rate was specific to vasopressin neurons because oxytocin neuron firing rate was unaffected by the induction of hypertension. Intravenous injection of the α1 ‐adrenoreceptor agonist, phenylephrine (2.5 μg/kg), transiently increased mean arterial blood pressure to cause a baroreflex‐induced inhibition of heart rate and vasopressin neuron firing rate (by 52 ± 9%) in non‐hypertensive rats. By contrast, intravenous phenylephrine did not inhibit vasopressin neurons in hypertensive rats, despite a similar increase in mean arterial blood pressure and inhibition of heart rate. Circulating angiotensin II can excite vasopressin neurons via activation of afferent inputs from the subfornical organ. However, the increase in vasopressin neuron firing rate and the loss of inhibition by intravenous phenylephrine were not blocked by intra‐subfornical organ infusion of the angiotensin AT1 receptor antagonist, losartan. It can be concluded that increased vasopressin neuron activity at the onset of hypertension is driven, at least in part, by reduced baroreflex inhibition of vasopressin neurons and that this might exacerbate the increase in blood pressure at the onset of hypertension. Abstract : Vasopressin constricts blood vessels and its release is normally inhibited by increased blood pressure. Here, we show that vasopressin neurons are paradoxically excited during the induction of moderate hypertension via a switch in baroreflex inhibition of vasopressin neurons to excitation. Hence, vasopressin neuron excitation might exacerbate the development of hypertension.